Ceramics and the Spanish Conquest - Hernández Sánchez, Gilda (Early Americas: History and Culture, 2012)
The Spanish colonization dramatically interrupted the autonomous development of ancient Mesoamerican culture. Nevertheless, indigenous societies learnt to live with the conquest. It was not only a time of crisis, but also an extraordinarily creative time period in which material culture reflected indigenous peoples' varied responses and adaptations to the changing circumstances. This work presents insights into the process of cultural continuity and change in the indigenous world by focusing on pottery technology in the Nahua (Aztec) region of Central Mexico. The late pre-colonial, early colonial and present-day characteristics of this industry are explored in order to come to a renewed understanding of its long-term development.